Do Antimicrobial Photodynamic Therapy and Low-Level Laser Therapy Minimize Postoperative Pain and Edema After Molar Extraction? - Fraga, Renato Silva; Antunes, Lívia Azeredo Alves; Fialho, Walter Luis Soares; Valente, Maria Isabel; Gomes, Cinthya Cristina; Fontes, Karla Bianca Fernandes Costa; Antunes, Leonardo Santos (Journal of oral and maxillofacial surgery, 2020)
This study was designed to examine the efficacy of antimicrobial photodynamic therapy (aPDT) and low-level laser therapy (LLLT) in reducing postoperative pain and edema after molar extractions. The investigators designed a single-blind randomized controlled study and enrolled subjects requiring extraction of at least one of the first or second molars. They were randomized to one of the following four groups: control group, aPDT group, LLLT group, and aPDT and LLLT group. Patients were blinded to the group assigned. The outcome variables were postoperative pain and edema. Pain intensity was measured on a visual analog scale (recorded every day for 7 days after tooth extraction). Facial edema was assessed by measuring the perimeter between the tragus, base of the jaw, and labial commissure, which was recorded once before surgery and then on the third and seventh days after surgery. Other variables were age, sex, ethnicity, decayed/missing/filled teeth, and tooth types. Appropriate univariate and bivariate statistics were computed and statistical significance was set at a value of P < .05. The sample was composed of 40 patients with a mean age of 41.25 ± 13.97 years and 25 (62.5%) of them were women. There were 10 subjects in each treatment group. The mean of postoperative pain within the groups was associated with a significant continuous decrease over time (P < .05). Postoperative pain was lowest in the aPDT + LLLT group in the 1st, 2nd, 3rd, 5th, 6th, and 7th day after tooth extraction (P < .05). There were no significant differences in edema among the groups (P > .05). The combined use of aPDT and LLLT was effective in reducing postoperative pain. These procedures can be applied in everyday surgical practice.